Reducing Cycle Time at an IBM Wafer Fabrication Facility - DEMEESTER, Lieven (Institutional Knowledge at Singapore Management University, 1996)
In 1991, IBM San Jose decided to produce and sell magnetic heads for computer disk drives on the open market to original equipment manufacturers. However, as IBM's wafer fabrication facility increased the number of products it manufactured, its manufacturing cycle time lengthened. Since cycle time is important in competing in the open market, IBM San Jose formed a study team (in cooperation with UCLA) to examine the wafer fab and to develop ways to reduce cycle time. The team designed a new production control system and proposed new performance measures for operators and engineers. IBM implemented the new production control system and established the performance measures in June 1992, and the cycle time decreased by 50 percent by the end of 1992.